Why Don’t I Help You? The Relationship between Role Stressors and Helping Behavior from a Cognitive Dissonance Perspective - Zhang, Li; Xia, Ying; Liu, Baowei; Han, Lu (Frontiers in Psychology, 2018)
This paper proposes that role stressor decreases helping behavior by undermining employees’ normative commitment based on cognitive dissonance perspective and social exchange theory. We also propose two competitive assumptions of the moderating effect of perceived organizational support. In this paper, we first examine these hypotheses in Study 1 and then verify the cognitive dissonance perspective in Study 2. In Study 1, we collected data from 350 employees of two Chinese enterprises. The results indicated that role stressor had a negative link with helping behavior via the mediating role of normative commitment. The results also showed that perceived organizational support strengthened the negative relationship between role stressor and normative commitment. In Study 2, we invited 104 employees to participate in a scenario experiment. The results found that role stressor had an impact on normative commitment via dissonance. Our studies verified the combination of cognitive dissonance perspective and social exchange theory to explain the impact of role stressors on helping behavior.